Flow-diverter stenting in post-traumatic pseudoaneurysm of cavernous internal carotid artery with epistaxis. Issue 3 (June 2015) - Giorgianni, Andrea; Pellegrino, Carlo; Minotto, Renzo; Mercuri, Anna; Baruzzi, Fabio; Cantoni, Alfredo; Cardim, Larissa Nocchi; Valvassori, Luca
This paper is a case report of a young patient after a major head trauma causing multiple skull base fractures. The trauma occasioned pseudoaneurysm (PSA) from intracavernous C4 segment of left internal carotid artery (ICA) protruding in the sphenoidal sinus. After two months, two episodes of massive epistaxis occurred. Consequently, the post-traumatic PSA was treated, after carotid occlusion test, with flow-diverter stent positioning. A computed tomography angiography study performed in the following days showed complete resolution of the post-traumatic PSA lesion and ICA patency.